On the beat: police and community problem solving - Skogan, Wesley G. (Westview Press, 1999)
1. Introduction -- 2. Chicago's model for problem solving -- 3. Organizational desing for problem solving -- 4. Training the public and the police -- 5. Neighborhood problems -- 6. Community capacity for problem solving -- 7. The police and problem solving -- 8. Conclusions and recommendations.